Pengaruh Fasilitas Hotel Dan Kualitas Pelayanan Terhadap Kepuasan Tamu di Hotel Whiz Prime Padang - Salsa Nabila Edha Hidayatia; Rahmi Fadilah (Tamasya : Jurnal Pariwisata Indonesia, 2025)
This study aims to analyze the influence of hotel facilities and service quality on guest satisfaction at Hotel Whiz Prime Padang. The background of this study is based on the importance of maintaining and improving the quality of hotel services and facilities in order to meet guest expectations and maintain customer loyalty amidst the increasingly tight competition in the hotel industry. This study uses a quantitative approach with a causal associative descriptive method. Data collection was carried out by distributing questionnaires to 379 respondents who had stayed at Hotel Whiz Prime Padang. The data analysis technique used was multiple linear regression with the help of SPSS version 22.The results showed that hotel facilities and service quality had a positive and significant effect on guest satisfaction. The coefficient of determination (R²) value of 0.739 indicates that 73.9% of the variation in guest satisfaction can be explained by hotel facilities and service quality significantly, while the rest is influenced by other variables outside this study. This finding indicates that the better the quality of facilities and services provided by the hotel, the higher the level of guest satisfaction will be. Therefore, the management of Hotel Whiz Prime Padang needs to evaluate and improve aspects of physical facilities as well as staff competence and attitudes in providing services to maintain guest satisfaction and loyalty.